Thermoplastic foam injection moulding of sandwich structures with short fibre-reinforced skin layers. (January 2021) - Loypetch, N; Tröltzsch, J; Nestler, D; Kroll, L; Siengchin, S
Sandwich structures, consisting of a short glass fibre–reinforced polypropylene film as skin layer and chemically blown polypropylene as the core material, were produced via injection moulding. The skin layers of the sandwich structures, which contain polypropylene as well as 30 wt% and 50 wt% of glass fibres namely polypropylene–glass fibres 30 and polypropylene–glass fibres 50 respectively, were produced by film extrusion using a coat hanger die. The properties of the films were investigated by dynamic mechanical analysis. Furthermore, the influence of different glass fibre contents in the skin layers and chemical blowing agent contents in the core material of sandwich structures was studied to compare them with the compact polypropylene and the polypropylene foams. The sandwich structures were characterized with regard to density, microstructure, weight reduction, surface roughness and bending properties. In general, distinctive reinforcement effect was achieved by use of the short glass fibre with the strong influence of processing direction of the film. For the sandwich structures, it was found that a good adhesion between the skin layers and the core material can be achieved during injection moulding. The microstructure and the bending properties of the sandwich structures depend on the glass fibre–reinforced film and the chemically blown core. It was found that the use of the skin layers led to lower cell intensity in the foam core. Nevertheless, a high modulus and strength to weight ratio could be accomplished by a high stiffness of the glass fibre–reinforced film and a low density of the chemically blown core. Additionally, it was found that the surface roughness of the films could be reduced due to processing in injection moulding.